1998
DOI: 10.1111/0004-5608.00118
|View full text |Cite
|
Sign up to set email alerts
|

The Balkanization Metaphor in the Analysis of U.S. Immigration

Abstract: Recent social commentary and social science research invokes the term “balkanization” to describe geographical trends in contemporary U.S. society. For example, William Frey describes “demographic balkanization” as a “spatial segmentation of population by race‐ethnicity, class, and age across broad regions, states, and metropolitan areas . . . driven by both immigration and long distance internal migration patterns” (1996:760). We take issue with the use of the balkanization metaphor for two reasons. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 72 publications
0
37
0
2
Order By: Relevance
“…The target domains are mostly conceptual ones (belonging) (Lakoff 1987). According to Ellis and Wright (1998), literary metaphors surprise and stimulate imagination. With overuse they become banal and lose impact.…”
Section: Suggestionmentioning
confidence: 99%
“…The target domains are mostly conceptual ones (belonging) (Lakoff 1987). According to Ellis and Wright (1998), literary metaphors surprise and stimulate imagination. With overuse they become banal and lose impact.…”
Section: Suggestionmentioning
confidence: 99%
“…This view renders the Greater Toronto Area (GTA) as composed of antagonistic tribalisms clearly demarcated in city space. The guard's view of the GTA as the locus of unknown threats emanating from immigrant neighborhoods recalls the tropes of balkanization in which suspicion, violence, and segregation are presented as the likely future of the nation (Ellis and Wright 1998). While Canada is often celebrated for what Cole Harris (2001) has called postmodern patriotism in which Canadian nationalism is predicated on difference between at least the English, French and First Nations people, it has also been shown that this discourse of Canada's lack of nationness in fact occludes domination and oppression through multiculturalism (Teelucksingh 2006).…”
Section: Bordering the National In Urban Spacementioning
confidence: 99%
“…La relación entre movilidad de autóctonos y extranjeros ha dado lugar a dos aproximaciones teóricas contrapuestas: por un lado, la hipótesis sustentada en Frey, sobre la existencia de lo que se ha denominado como White flight, según la cual la entrada de inmigración extranjera favorece el proceso de suburbanización (Frey, 1995(Frey, y 1996; hipótesis contestada por Ellis y Wright, según los cuales los procesos de suburbanización generan nuevas oportunidades residenciales que son aprovechadas por la población inmigrante (Ellis y Wright, 1998). Para la movilidad dentro de una gran ciudad, recientemente, Stillwell y McNulty, han estudiado los cambios residenciales internos dentro de la ciudad de Londres, encontrando un proceso de dispersión desde las áreas de mayor concentración de minorías étnicas hacia las áreas con menor peso de éstas, situación válida para la mayoría de grupos considerados (Stillwell y McNulty, en imprenta).…”
Section: Marco Teóricounclassified